2015
DOI: 10.1586/14737175.2015.1038244
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s disease: a review of non-motor symptoms

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder resulting from degeneration of the substantia nigra and the dopaminergic nigrostriatal pathway. Most treatments are geared toward the management and relief of motor symptoms in Parkinson's patients; however, as the disease progresses, various complications can be observed. Non-motor symptoms (NMS) may arise simply from the disease itself and are highly destructive to quality of life. These symptoms include mood disorders, cognitive dysfunction, pain, sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
58
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 92 publications
0
58
0
11
Order By: Relevance
“…Depression is one of the most common mood disturbances in PD, but its pathogenesis is unclear . Studies using advanced neuroimaging generally suggest increased neural activity in the prefrontal regions and decreased functional connectivity between the prefrontal‐limbic networks in depressed PD patients .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Depression is one of the most common mood disturbances in PD, but its pathogenesis is unclear . Studies using advanced neuroimaging generally suggest increased neural activity in the prefrontal regions and decreased functional connectivity between the prefrontal‐limbic networks in depressed PD patients .…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson's disease (PD) is one of the most common neurodegenerative disorders, which have typical motor symptoms including resting tremor, rigidity, bradykinesia, and postural reflex abnormalities . Increasing studies have shown that most PD patients will experience a series of nonmotor symptoms such as paresthesia, sleep disorders, autonomic dysfunction, neuropsychiatric symptoms, and behavioral disorders . Depression is the most common neuropsychiatric symptom, and up to 50% PD patients have suffered from this psychiatric disorder .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PD is traditionally defined as a movement disorder resulting from a prominent loss of dopaminergic neurons of the nigrostriatal pathway, but more recently it has been demonstrated that widespread non-motor symptoms, such as cognitive impairment and mood disorders, are also prevalent, which involve extensive brain regions3456. PD is clinically and etiologically heterogeneous and its complex neurobiological underpinnings remain to be fully elucidated3.…”
mentioning
confidence: 99%
“…On the other hand, it is well known that PD can affect many non-motor systems. Chronic pain has been known to be part of PD, as many PD patients have reported differential pain [9], and levodopa has been shown to be associated with increased pain threshold in PD [10]. Thus, it is conceivable that higher chronic pain from limb injuries may represent the lower pain threshold in the pre-PD state.…”
Section: Discussionmentioning
confidence: 99%